Case reportHereditary neuropathy with liability to pressure palsy - Paprocka, Justyna; Kajor, Maciej; Jamroz, Ewa; Jesipowicz, Jacek; Seeman, Pavel; Marszał, Elżbieta (Folia Neuropathologica, 2006)
Hereditary neuropathy with liability to pressure palsy (HNPP) is an autosomal dominant disease with sensory and motor nerve palsies usually precipitated by trivial trauma or compression. In the majority of cases HNPP is caused by deletion of the peripheral myelin protein 22 gene (PMP22) on chromosome 17p11.2. The authors present a family case with genetically proven HNPP.